KINERJA KEUANGAN PADA PERTUMBUHAN LABA PERBANKAN DI BEI 2019 - 2021 - Mahendra, Ebnu; Solikah, Mar'atus; Zaman, Badrus (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study is to examine the effect of Return on Assets, Loan to Deposit, Total Assets Turnover, Net Profit Margin on profit growth in banks listed on the IDX in 2019-2021. How to collect data in the form of annual quarterly financial reports (annual reports) of banking companies from idx.co.id research technique is descriptive statistics and the data is collected an analysis using SPSS v24. Results of this study based on the t-test partially showing Return On Assets (.019), Total Assets Turnover (.000), Net Profit Margin (.010) have a significant effect and Loan to Deposit (.081) has no significant effect on growth profit. Conclusion of this research is analysis to determine the profit growth that is very necessary for the company from the data analysis we can find out and improve the assets are important and useful for the company and optimize.